Geologi Daerah Dimito dan Sekitarnya Kabupaten Boalemo Provinsi Gorontalo - Alifia Widya Warapsari Badaru; Fitryane Lihawa; Intan Noviantari Manyoe (Universitas Negeri Gorontalo, 2019)
Administratively, the research area covers two districts, Wonosari Sub-district and Dulupi Sub-district, Boalemo District, Gorontalo Province. Based on the physiography of the Gorontalo region, the research area which is included in the southern mountain zone of Bone-Tilamuta-Modello generally consists of ancient volcano-sedimentary rock formations in Gorontalo, the Eocene-Oligocene. The purpose of this geological research is to discover the geological order that developed in the area of Dimito and surrounding are as covering several aspect such as geomorphology, stratigraphy, geological structure, and geological history. The result shows that the geomorphology of the research area divided into three geomorphic units, namely the units of the Alluvial Plain, Volcanic Hills, and Denudasional Hills. Stratigraphy of the research area divided into five types of units sorted from the early Miocene to the Holocene, i.e., Lava Basal Dimito (Early Eocene), Wackestone Dimito (Early Eocene), Andesit Kalidingin (Middle Miocene), Granodiorite Bualo (Middle Pliocene), and Alluvial Buaolo (Recen). Geological structures that work on the location of the research area relatively trend from northeast-southwest to northwest-southeast. Fault working on the location of the research area from the data processing consists of Normal Left Slip Fault Kalidingin and Lag Left Slip Fault Bualo.